Coating iron plating method for highlight pearlescent magnetic powder

By adopting the steps of substrate pretreatment, film removal layer coating, substrate powder coating and iron plating treatment in the coating and plating process of high-gloss pearlescent magnetic powder, the problems of uniform distribution of pearlescent powder on the substrate and the density of the iron plating layer are solved, high gloss, uniform color and good adhesion are achieved, and the mechanical properties of the iron plating layer are improved.

CN119913508AInactive Publication Date: 2025-05-02GUANGDONG BAICAIYA CHEMICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510041000.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing method of coating and plating of high-gloss pearlescent magnetic powder is difficult to ensure the uniform distribution of pearlescent powder on the substrate and the density of the iron plating layer, resulting in poor gloss and color uniformity, insufficient adhesion, and the mechanical properties of the iron plating layer need to be improved.

Method used

The steps of substrate pretreatment, film defiling layer coating, substrate powder coating and iron plating are adopted, including ultrasonic cleaning, plasma treatment, electrostatic spraying and ion beam-assisted deposition, forming a dense, uniform coating structure and high-performance iron plating layer.

Benefits of technology

It realizes the uniform distribution of pearl powder on the substrate and the density and mechanical properties of the iron plated layer, improves gloss, color uniformity and adhesion, extends the service life of the product, and broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236943400000071
    Figure BDA0005236943400000071
  • Figure BDA0005236943400000081
    Figure BDA0005236943400000081
  • Figure BDA0005236943400000082
    Figure BDA0005236943400000082
Patent Text Reader

Abstract

The invention provides a coating and iron plating method for high-gloss pearlescent magnetic powder. The coating and iron plating method comprises the steps of matrix pretreatment, demolding layer coating, matrix powder coating, iron plating treatment, anti-oxidation treatment, demolding, post-treatment and the like. In matrix pretreatment, pearlescent matrix powder is cleaned, dried and subjected to surface activation treatment, so that the surface activity and roughness of the pearlescent matrix powder are improved. And in the step of coating the demolding layer, the PET film is coated with a sodium chloride solution, and drying is carried out. The base powder is coated by adopting high-voltage electrostatic spraying and blade coating, so that the pearl powder forms a compact and uniform coating structure on the PET film. Iron plating treatment is carried out in a vacuum environment, ion beams are applied to assist deposition, and a compact and firm iron plating layer is formed. And finally, carrying out anti-oxidation treatment, demolding and post-treatment to obtain the high-gloss pearlescent magnetic powder meeting the requirements. According to the method, the coating uniformity of the highlight pearlescent magnetic powder and the mechanical performance of the iron plating layer are improved by optimizing parameters and processes of all the steps, and powerful technical support is provided for application in related fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pearlescent pigment coating, in particular to a method for coating and iron plating high-gloss pearlescent magnetic powder. Background Art

[0002] With the continuous development of science and technology, high-gloss pearlescent magnetic powder is increasingly used in various fields, such as coatings, inks, plastics, rubber and other industries. Its unique optical effects and magnetic properties bring richer visual effects and functional characteristics to the products. However, in the existing technology, the coating and iron plating method of high-gloss pearlescent magnetic powder still has some shortcomings.

[0003] On the one hand, traditional coating methods often make it difficult to ensure uniform distribution of pearlescent powder on the substrate, resulting in poor gloss and color uniformity of the coating. In addition, the adhesion of the coating is often limited, and it is easy to fall off or peel off, thus affecting the service life and aesthetics of the product.

[0004] On the other hand, in the iron plating process, the existing technology often makes it difficult to form a dense and strong iron plating layer. The thickness and uniformity of the iron plating layer are difficult to control, and the mechanical properties of the iron plating layer also need to be improved. This limits the application of high-gloss pearlescent magnetic powder in certain high-end fields, such as automobiles, electronics, aerospace and other industries.

[0005] In summary, the existing preparation technology of pearlescent magnetic powder has shortcomings in many aspects such as base powder processing, coating process, and iron plating process. A new coating and iron plating method with better comprehensive performance is urgently needed to meet the growing market demand and higher product performance requirements. Summary of the invention

[0006] In view of this, the present invention proposes a method for coating and plating high-gloss pearlescent magnetic powder to solve the above problems. The technical solution of the present invention is implemented as follows: A method for coating and plating high-gloss pearlescent magnetic powder:

[0007] S1. Matrix pretreatment: washing, drying and surface activation of the pearlescent matrix powder to make the surface of the pearlescent powder matrix have uniform and appropriate active sites;

[0008] S2, coating of release layer: pre-treat the PET film of the coating machine with pulse electric field for 2-5 minutes, then coat the PET film with sodium chloride solution, the coating thickness is 50-1000nm, and the coated PET film is rolled up and dried in a drying temperature zone of 100-180℃;

[0009] S3, base powder coating: the dried PET film is sprayed with pearl powder base powder by high-voltage electrostatic spraying in the second coating area. Electrostatic spraying can make the pearl powder more evenly distributed on the surface of the PET film under the action of the electric field, and can improve the initial adhesion of the pearl powder to the PET film. Then, the coating is carried out, and the coating thickness is controlled at 200-600nm. The coating process can further smooth the coating, so that the pearl powder and the binder form a more dense and uniform coating structure on the PET film, and at the same time, the agglomerated particles and bubbles that may be generated during the spraying process are removed. The PET film coated with pearl powder is rolled up again and dried in a temperature zone of 130-180°C;

[0010] S4, iron plating treatment: the PET film after drying enters the vacuum iron plating area for iron plating, and the vacuum degree is (1-5)×10 -3 Pa, and ion beam assisted deposition is applied at the same time. The ion beam bombards the surface of the pearlescent powder PET film where the iron layer is being deposited. The iron plating thickness is 50-300nm. The bombardment of the ion beam can clean the trace impurities that may remain on the surface of the pearlescent powder, further activate the surface, and enable the deposited iron atoms to obtain higher kinetic energy on the film surface, so as to more closely combine with the pearlescent powder and the binder to form a denser and firmer iron plating layer. At the same time, ion beam assisted deposition can also improve the crystal structure of the iron plating layer, making it finer and more uniform, and improve the mechanical properties of the iron plating layer;

[0011] S5, anti-oxidation treatment and film stripping: After the iron plating is completed, silica sol is coated in the three-coating area to protect the elemental iron from oxidation, with a thickness of 40-60nm. After water washing, pure water washing dissolves sodium chloride for film stripping;

[0012] S6. Post-processing: The powder removed from the film is ultrasonically crushed to make the powder state more in line with the requirements.

[0013] Furthermore, the preparation method of the matrix powder pretreatment of S1 is:

[0014] S11, cleaning: adding cleaning solution to the base powder with a particle size of 10-50nm and using ultrasonic cleaning for 15-30min. The cleaning solution is a mixed solution of deionized water and a surfactant in a volume ratio of 3:1-2. After cleaning, drying is performed.

[0015] S12, surface activation treatment: the dried base powder is treated with plasma, the treatment gas is a mixed gas of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:3-5, the gas flow rate is controlled at 20-100 sccm, and the treatment time is 5-10 minutes, so as to improve the activity and roughness of the pearl powder base surface;

[0016] S13, surface sealing treatment: a layer of adhesive layer is applied to the base powder after surface activation treatment. The adhesive is a mixture of methyl silicone resin and polyurethane resin in a mass ratio of 2:1-3:1. The coating method is electrostatic spraying with a coating thickness of 0.5-1.5μm, and then cured at 60-80℃ for 10-20min to enhance the bonding force between the iron layer and the pearl powder base.

[0017] Furthermore, the surfactant in S11 is selected from any one or a combination of polyethylene glycol octylphenyl ether, cocamidopropyl betaine, dodecyl dimethyl betaine or hexadecyl trimethyl ammonium bromide.

[0018] Furthermore, the S12 plasma treatment has a processing power of 100-200 W and a frequency of 13.56-40.68 MHz.

[0019] Furthermore, the mass concentration of the sodium chloride solution in S2 is 70-90%.

[0020] Furthermore, in the S2 pulse electric field pretreatment, the pulse electric field strength is 30-80 kV / cm, and the pulse frequency is 50-200 Hz. Through this pulse electric field treatment, the molecular structure on the surface of the PET film will undergo directional polarization and slight ionization, so that more active sites are generated on the film surface and the surface energy is improved, providing a more favorable adsorption basis for the subsequent coating of pearlescent powder and enhancing the adhesion between the pearlescent powder and the PET film.

[0021] Furthermore, the S3 applies an electrostatic voltage of 60-100 kV at the nozzle, and the spraying flow rate is 10-30 ml / min.

[0022] Furthermore, the scraping speed of S3 is 5-15 cm / s, and the scraping pressure is 0.5-2 N / cm 2 .

[0023] Furthermore, the ion beam of S4 is an argon ion beam, the energy of the argon ion beam is 100-500eV, and the beam current density is 0.5-2mA / cm 2 .

[0024] Furthermore, the ultrasonic crushing power of S6 is 200-400W and the frequency is 15-30kHz.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The method for coating and iron plating of high-gloss pearlescent magnetic powder proposed in this scheme uses ultrasonic cleaning of a mixed solution of deionized water and a specific surfactant and plasma treatment of oxygen and argon gas to deeply clean the base powder and produce uniform active sites and suitable roughness during the base pretreatment stage. The mixed binder of methyl silicone resin and polyurethane resin is electrostatically sprayed and cured to effectively enhance the bonding force between the iron layer and the base, laying a good foundation. When coating the stripping layer, the PET film is pretreated with a pulsed electric field to improve the surface activity and adhesion. After being coated with a sodium chloride solution of a specific concentration and dried, it provides a stable base layer for the subsequent coating. In the base powder coating stage, high-voltage electrostatic spraying combined with precise parameters makes the pearlescent powder evenly distributed, and scraping removes defects to form a dense and uniform coating, ensuring the stability of optical and magnetic properties and mechanical properties. In the iron plating process, argon ion beam-assisted deposition is used under high vacuum to clean impurities, activate the surface, optimize the bonding of iron atoms and improve the crystal structure, improve the mechanical properties of the iron plating layer, and adapt it to complex environments. In addition, the anti-oxidation treatment of silica sol further extends the service life of the product, and the automation and continuity of the entire process improve production efficiency and product quality. Therefore, this method not only optimizes the performance of high-gloss pearlescent magnetic powder, but also broadens its application range, bringing significant technological progress and economic benefits to related industries. DETAILED DESCRIPTION

[0027] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0028] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0029] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0030] Example 1

[0031] A method for coating and iron plating high-gloss pearlescent magnetic powder comprises the following steps:

[0032] S1. Matrix pretreatment: cleaning, drying and surface activation of pearlescent matrix powder;

[0033] S11, cleaning: adding cleaning solution to the base powder with a particle size of 10 nm and using ultrasonic cleaning for 15 minutes. The cleaning solution is a mixed solution of deionized water and dodecyl dimethyl betaine in a volume ratio of 3:1. After cleaning, drying is performed.

[0034] S12, surface activation treatment: the dried base powder is treated with plasma, the treatment gas is a mixed gas of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:3, the gas flow rate is controlled at 20 sccm, the treatment power is 100 W, the frequency is 13.56 MHz, and the treatment time is 5 min;

[0035] S13, surface sealing treatment: a layer of adhesive layer is applied to the base powder after surface activation treatment, wherein the adhesive is a mixture of methyl silicone resin and polyurethane resin in a mass ratio of 2:1, and the coating method is electrostatic spraying, the coating thickness is 0.5 μm, and then cured at 60° C. for 10 minutes;

[0036] S2, coating of release layer: pre-treat the PET film of the coating machine with pulse electric field for 2 minutes, the pulse electric field strength is 30kV / cm, the pulse frequency is 50Hz, and then coat the PET film with a sodium chloride solution with a mass concentration of 70% and a coating thickness of 50nm. The coated PET film is rolled up and dried in a drying temperature zone of 100°C;

[0037] S3, base powder coating: the dried PET film is sprayed with pearl powder base powder in the secondary coating area by high voltage electrostatic spraying, 60kV electrostatic voltage is applied to the nozzle, the spray flow rate is 10ml / min, and then scraping is performed, the scraping speed is 5cm / s, and the scraping pressure is 0.5N / cm 2 , the coating thickness is controlled at 200nm, the PET film coated with pearlescent powder is rolled up again and dried in a 130℃ temperature zone;

[0038] S4, iron plating treatment: the PET film after drying enters the vacuum iron plating area for iron plating, and the vacuum degree is 1×10 -3 Pa, and ion beam assisted deposition was applied at the same time. The ion beam of S4 was an argon ion beam with an energy of 100 eV and a beam current density of 0.5 mA / cm 2 , the iron plating thickness is 50nm;

[0039] S5, anti-oxidation treatment and film stripping: After the iron plating is completed, the three-coating area is coated with silica sol with a thickness of 40nm, and then washed with pure water to dissolve sodium chloride for film stripping;

[0040] S6. Post-processing: The powder removed from the film is ultrasonically crushed with an ultrasonic power of 200W and a frequency of 15kHz to make the powder state more in line with the requirements.

[0041] Example 2

[0042] A method for coating and iron plating high-gloss pearlescent magnetic powder comprises the following steps:

[0043] S1. Matrix pretreatment: cleaning, drying and surface activation of pearlescent matrix powder;

[0044] S11, cleaning: adding cleaning solution to the base powder with a particle size of 50nm and using ultrasonic cleaning for 30min. The cleaning solution is a mixed solution of deionized water and polyethylene glycol octylphenyl ether in a volume ratio of 3:2. After cleaning, drying is performed.

[0045] S12, surface activation treatment: the dried base powder is treated with plasma, the treatment gas is a mixed gas of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:5, the gas flow rate is controlled at 100 sccm, the treatment power is 200 W, the frequency is 40.68 MHz, and the treatment time is 10 min;

[0046] S13, surface sealing treatment: a layer of adhesive layer is applied to the base powder after surface activation treatment, wherein the adhesive is a mixture of methyl silicone resin and polyurethane resin in a mass ratio of 3:1, and the coating method is electrostatic spraying, the coating thickness is 1.5 μm, and then cured at 80° C. for 20 minutes;

[0047] S2, coating of release layer: pre-treat the PET film of the coating machine with pulse electric field for 5 minutes, the pulse electric field strength is 80 kV / cm, the pulse frequency is 200 Hz, and then a sodium chloride solution with a mass concentration of 90% is coated on the PET film, and the coating thickness is 1000 nm. The coated PET film is rolled up and dried in a drying temperature zone at 180°C;

[0048] S3, base powder coating: the dried PET film is sprayed with pearl powder base powder in the secondary coating area by high voltage electrostatic spraying, 100kV electrostatic voltage is applied to the nozzle, the spray flow rate is 30ml / min, and then scraping is performed, the scraping speed is 15cm / s, and the scraping pressure is 2N / cm 2 , the coating thickness is controlled at 600nm, the PET film coated with pearlescent powder is rolled up again and dried in a 180℃ temperature zone;

[0049] S4, iron plating treatment: the PET film after drying enters the vacuum iron plating area for iron plating, and the vacuum degree is 5×10 -3 Pa, and ion beam assisted deposition was applied at the same time. The ion beam of S4 was an argon ion beam with an energy of 500 eV and a beam current density of 2 mA / cm 2 , the iron plating thickness is 300nm;

[0050] S5, anti-oxidation treatment and film stripping: After the iron plating is completed, the three-coating area is coated with silica sol with a thickness of 60nm, and then washed with pure water to dissolve sodium chloride for film stripping;

[0051] S6. Post-processing: The powder removed from the film is ultrasonically crushed with an ultrasonic power of 400W and a frequency of 30kHz to make the powder state more in line with the requirements.

[0052] Example 3

[0053] A method for coating and iron plating high-gloss pearlescent magnetic powder comprises the following steps:

[0054] S1. Matrix pretreatment: cleaning, drying and surface activation of pearlescent matrix powder;

[0055] S11, cleaning: adding cleaning solution to the base powder with a particle size of 30nm and using ultrasonic cleaning for 25min. The cleaning solution is a mixed solution of deionized water and cocamidopropyl betaine in a volume ratio of 3:2. After cleaning, drying is performed.

[0056] S12, surface activation treatment: the dried base powder is treated with plasma, the treatment gas is a mixed gas of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:4, the gas flow rate is controlled at 60 sccm, the treatment power is 150 W, the frequency is 30.68 MHz, and the treatment time is 8 min;

[0057] S13, surface sealing treatment: a layer of adhesive layer is applied to the base powder after surface activation treatment, wherein the adhesive is a mixture of methyl silicone resin and polyurethane resin in a mass ratio of 3:1, and the coating method is electrostatic spraying, the coating thickness is 1 μm, and then cured at 70° C. for 15 minutes;

[0058] S2, coating of release layer: pre-treat the PET film of the coating machine with pulse electric field for 3 minutes, with pulse electric field strength of 50 kV / cm and pulse frequency of 150 Hz, and then coat the PET film with sodium chloride solution with mass concentration of 80% and coating thickness of 500 nm. The coated PET film is rolled up and dried in a drying temperature zone at 150° C.;

[0059] S3, base powder coating: the dried PET film is sprayed with pearl powder base powder in the secondary coating area by high voltage electrostatic spraying, 80kV electrostatic voltage is applied to the nozzle, the spray flow rate is 20ml / min, and then scraping is performed, the scraping speed is 10cm / s, and the scraping pressure is 1.5N / cm 2 , the coating thickness is controlled at 400nm, the PET film coated with pearlescent powder is rolled up again and dried in a temperature zone of 150℃;

[0060] S4, iron plating treatment: the PET film after drying enters the vacuum iron plating area for iron plating, and the vacuum degree is 3×10 -3 Pa, and ion beam assisted deposition was applied at the same time. The ion beam of S4 was an argon ion beam with an energy of 300 eV and a beam current density of 1.5 mA / cm 2 , the iron plating thickness is 200nm;

[0061] S5, anti-oxidation treatment and film stripping: After the iron plating is completed, the three-coating area is coated with silica sol with a thickness of 50nm, and then washed with pure water to dissolve sodium chloride for film stripping;

[0062] S6. Post-processing: The powder removed from the film is ultrasonically crushed with an ultrasonic power of 300W and a frequency of 25kHz to make the powder state more in line with the requirements.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 3 is that no surface activation treatment and sealing layer are performed in S1.

[0065] Preparation method of S1 base powder pretreatment:

[0066] S11, cleaning: adding a cleaning solution to the base powder with a particle size of 30 nm and performing ultrasonic cleaning for 25 min. The cleaning solution is a mixed solution of deionized water and cocamidopropyl betaine in a volume ratio of 3:2. After cleaning, the powder is dried.

[0067] Comparative Example 2

[0068] The difference between this comparative example and Example 3 is that the base powder coating method of S3 is air spraying, the air pressure is 0.5 MPa, the distance between the spray gun and the PET film is maintained at 20 cm, and the spraying flow rate is 20 ml / min.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 3 is that ion beam assisted deposition is not applied in the iron plating process of S4. Specifically, the PET film after drying is iron plated in the vacuum iron plating area, and the vacuum degree is 3×10 -3 Pa, the iron plating thickness is 200nm.

[0071] 1. Magnetic performance test:

[0072] The hysteresis loop of the high gloss pearlescent magnetic powder was measured using a vibrating sample magnetometer (VSM). The saturation magnetization (Ms), residual magnetization (Mr) and coercive force (Hc) parameters of the magnetic powder were obtained through the hysteresis loop.

[0073] Table 1:

[0074]

[0075]

[0076] As can be seen from Table 1, the saturation magnetization (Ms), residual magnetization (Mr) and coercive force (Hc) of Example 1, Example 2 and Example 3 are all higher than those of Comparative Example 1, Comparative Example 2 and Comparative Example 3. This shows that the high-gloss pearlescent magnetic powder in the examples has better magnetic properties. Among them, the magnetic properties of Example 3 are the best, and its saturation magnetization, residual magnetization and coercive force all reach a relatively high level.

[0077] 2. Optical performance test:

[0078] (1) Gloss test: Use a gloss meter, place the instrument on the sample surface, irradiate light at a fixed angle (60°, 80°) and measure the intensity of the reflected light to obtain the gloss value.

[0079] (2) Color measurement: Use a spectrophotometer to detect the brightness of the high-gloss pearlescent magnetic powder (L* value). By comparing the color changes before and after iron plating, the impact of the iron plating process on the color of the pearlescent powder can be evaluated to ensure that the product color meets the expected application requirements.

[0080] Table 2:

[0081]

[0082] According to Table 2, Examples 1, 2 and 3 are superior to the comparative example in glossiness at 60° and 80° and brightness (L* value). The high gloss pearlescent magnetic powders in the examples have higher glossiness and brightness, which makes them have better performance in optical applications.

[0083] 3. Coating performance test:

[0084] (1) Coating uniformity test: Use a magnetic thickness gauge to select 10 areas on the iron-plated layer to test the thickness mean, standard deviation, coefficient of variation and other statistical indicators to quantify the coating uniformity.

[0085] Rating criteria:

[0086] Grade A: standard deviation σ≤0.25μm, coating uniformity is very good, coating thickness or glue coating amount distribution is very consistent;

[0087] Grade B: 0.25μm<σ≤0.50μm, the coating uniformity is good, and the coating thickness or glue coating amount distribution is relatively consistent;

[0088] Grade C: 0.50μm<σ≤0.75μm, the coating uniformity is general, and there are certain differences in the coating thickness or glue coating amount distribution;

[0089] Grade D: σ>0.75μm, coating uniformity is poor, and coating thickness or glue coating amount distribution varies greatly.

[0090] (2) Adhesion test: The cross-cut method is used to test the adhesion of the high-gloss pearlescent magnetic powder coating on the PET film. The cross-cut method is to draw squares on the coating surface, then stick them with tape and tear them off, and observe the shedding of the coating in the squares to evaluate the adhesion level.

[0091] Rating criteria:

[0092] Level 0: The cutting edge is completely smooth, without any falling off;

[0093] Level 1: A small amount of coating falls off at the intersection of the cuts, but the cross-cut area affected cannot be significantly greater than 5%.

[0094] Level 2: Coating is peeled off at the intersection of the cuts and / or along the edges of the cuts. The affected cross-cut area is significantly greater than 5%, but not significantly greater than 15%.

[0095] Level 3: The coating is partially or completely detached in large pieces along the cut edges and / or partially or completely peeled off at different locations on the grid. The affected cross-cut area is significantly greater than 15%, but not significantly greater than 35%.

[0096] Grade 4: The coating is flaking off in large pieces along the cut edges, and / or some squares are partially or completely detached.

[0097] The cross-cut area affected was significantly greater than 35%.

[0098] Table 3:

[0099]

[0100] As can be seen from Table 3, Examples 1, 2, and 3 all performed well in coating uniformity rating and adhesion grade, reaching Grade A and Grade 0. This indicates that they have good coating uniformity and adhesion, and can meet the requirements of high-quality coating.

[0101] 4. Chemical stability test

[0102] (1) Corrosion resistance test: A salt spray test is used to evaluate the corrosion resistance of high-gloss pearlescent magnetic powder. The PET film sample coated with high-gloss pearlescent magnetic powder is placed in a salt spray test chamber and tested according to standard salt spray test conditions (sodium chloride solution concentration of 5%, temperature of 35°C, spray time of 72 hours). Observe whether the iron plating layer and pearlescent powder coating show corrosion, discoloration or peeling in the salt spray environment.

[0103] (2) Acid and alkali resistance: Prepare a 0.1 mol / L hydrochloric acid solution, place the pearl powder sample in it, and soak it at 25°C for 10 hours. Prepare a 0.1 mol / L sodium hydroxide solution, place the pearl powder sample in it, and soak it at 40°C for 10 hours. Test their mass loss rates respectively.

[0104] Mass loss rate = (mass before immersion - mass after immersion) / mass before immersion × 100%.

[0105] Table 4:

[0106]

[0107]

[0108] According to Table 4, in the salt spray test, Examples 1-3 showed no change after 72 hours of testing, indicating that the iron plating layer and the pearlescent powder coating have excellent corrosion resistance and can maintain good performance in a high salt spray environment. In the hydrochloric acid and sodium hydroxide immersion tests, the mass loss rates of Examples 1, 2 and 3 are all low, indicating that they have good acid and alkali resistance.

[0109] In summary, Example 3 has the best performance effect. Compared with Comparative Example 1, the surface activation treatment and sealing of the pearlescent matrix powder can make the surface of the pearlescent powder matrix have uniform and appropriate active sites, and enhance the chemical adsorption between the matrix surface and the subsequent coating material. The surface sealing layer can effectively enhance the bonding force between the iron layer and the pearlescent powder matrix, prevent the iron layer from peeling off from the pearlescent powder matrix, and ensure the integrity of the material and the stability of the performance.

[0110] Compared with Comparative Example 2, electrostatic spraying can make the pearlescent powder more evenly distributed on the surface of the PET film under the action of the electric field, and can improve the initial adhesion of the pearlescent powder to the PET film, while making the pearlescent powder base powder charged under the action of the electric field. Since charges of the same kind repel each other, the pearlescent powder will be dispersed as much as possible on the surface of the PET film, thereby achieving a more uniform distribution.

[0111] Compared with Comparative Example 3, ion beam assisted deposition is applied simultaneously during the iron plating process. The bombardment of the ion beam can remove impurities from the surface, further activate the surface, and enable the deposited iron atoms to obtain higher kinetic energy on the film surface, thereby more closely combining with the pearlescent powder and the binder to form a denser and firmer iron plating layer. At the same time, ion beam assisted deposition can also improve the crystal structure of the iron plating layer, making it finer and more uniform, and improve the mechanical properties of the iron plating layer.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for coating and iron plating high-gloss pearlescent magnetic powder, characterized in that: The following steps are involved: S1. Matrix pretreatment: cleaning, drying and surface activation of pearlescent matrix powder; S2, coating of release layer: pre-treat the PET film of the coating machine with pulse electric field for 2-5 minutes, then coat the PET film with sodium chloride solution, the coating thickness is 50-1000nm, and the coated PET film is rolled up and dried in a drying temperature zone of 100-180℃; S3, base powder coating: the dried PET film is sprayed with pearl powder base powder in the second coating area by high voltage electrostatic spraying, and then scraped, and the coating thickness is controlled at 200-600nm. The PET film coated with pearl powder is rolled up again and dried in a temperature zone of 130-180℃; S4, iron plating treatment: the PET film after drying enters the vacuum iron plating area for iron plating, and the vacuum degree is (1-5)×10 -3 Pa, while applying ion beam assisted deposition, the iron plating thickness is 50-300nm; S5, anti-oxidation treatment and film stripping: After the iron plating is completed, the three-coating area is coated with silica sol with a thickness of 40-60nm, and then washed with pure water to dissolve sodium chloride for film stripping; S6. Post-processing: The powder removed from the film is ultrasonically crushed to make the powder state more in line with the requirements.

2. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The preparation method of the base powder pretreatment of S1: S11, cleaning: adding cleaning solution to the base powder with a particle size of 10-50nm and using ultrasonic cleaning for 15-30min. The cleaning solution is a mixed solution of deionized water and a surfactant in a volume ratio of 3:1-2. After cleaning, drying is performed. S12, surface activation treatment: the dried base powder is treated with plasma, the treatment gas is a mixed gas of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:3-5, the gas flow rate is controlled at 20-100 sccm, and the treatment time is 5-10 min; S13, surface sealing treatment: a layer of adhesive layer is applied to the base powder after surface activation treatment, wherein the adhesive is a mixture of methyl silicone resin and polyurethane resin in a mass ratio of 2:1-3:1, and the coating method is electrostatic spraying, the coating thickness is 0.5-1.5 μm, and then cured at 60-80°C for 10-20 minutes.

3. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 2, characterized in that: The surfactant in S11 is selected from any one or a combination of polyethylene glycol octylphenyl ether, cocamidopropyl betaine, dodecyl dimethyl betaine or hexadecyl trimethyl ammonium bromide.

4. The method for coating and iron plating high-gloss pearlescent magnetic powder as claimed in claim 2, characterized in that: The S12 plasma treatment has a processing power of 100-200 W and a frequency of 13.56-40.68 MHz.

5. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The mass concentration of the sodium chloride solution in S2 is 70-90%.

6. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: In the S2 pulse electric field pretreatment, the pulse electric field strength is 30-80 kV / cm and the pulse frequency is 50-200 Hz.

7. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The S3 applies an electrostatic voltage of 60-100 kV at the nozzle, and the spraying flow rate is 10-30 ml / min.

8. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The scraping speed of S3 is 5-15cm / s, and the scraping pressure is 0.5-2N / cm 2 .

9. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The ion beam of S4 is an argon ion beam with an energy of 100-500 eV and a beam current density of 0.5-2 mA / cm 2 .

10. The method for coating and iron plating high-gloss pearlescent magnetic powder according to claim 1, characterized in that: The ultrasonic crushing power of S6 is 200-400W, and the frequency is 15-30kHz.

Citation Information

Cited By

  • Production method of magnetic pearlescent effect pigment

    CN121136478A